Semi-reactive Switch Based Proxy ARP in SDN - Fauzi Dwi Setiawan Sumadi; Diah Risqiwati; Syaifuddin Syaifuddin (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
In order to achieve high scalability during the network discovery process in software-defined networking (SDN), an extensive method for generating switch-based proxy is essential. This paper investigated the semi reactive solution for guiding the controller to build an OFPT_FLOW_MOD message that allowed SDN switch to reply an Address Resolution Protocol (ARP) request directly by deploying the semi-reactive switch-based proxy ARP application in northbound application programming interface (API). We conduct the experiment by using Open Networking Operating System (ONOS) an open-source SDN controller simulated in Mininet environment. As can be seen from the evaluation result, the installed application can reduce the ARP reaction time up to 95% calculated from the sender host. The final result also indicates that our approach can decrease the controller's loads significantly.